THE EFFECT OF COMPENSATION ON EMPLOYEE JOB SATISFACTION AT PT. TABALONG DRINKING WATER SHINES (PERSERODA) - Siska Anggreani; Saroyo (JAPB, 2023)
Most companies or agencies definitely want employees who have enthusiasm and satisfaction in carrying out their work, including PT. Tabalong Drinking Water Shines (Perseroda), which has many employees. This study aims to determine the effect of compensation on employee job satisfaction at PT. Tabalong Drinking Water Shines (Perseroda). The method used in this study is a quantitative method; data collection techniques include interviews, observation, and questionnaires. The measurement scale is a Likert scale. The data analysis in this study was done using simple linear regression analysis. This study uses the SPSS v26 data processing program. The results showed that there was an effect of compensation on employee job satisfaction at PT. Tabalong Drinking Water Shines (Perseroda). The magnitude of the effect of compensation (X) on employee job satisfaction (Y) at PT. Tabalong Drinking Water Shines (Perseroda) is 10.1%, and the remaining 89.9% is influenced by other variables. Based on the value of the correlation coefficient, the value of 0.101 (10.1%) includes a very low correlation. Keywords: Compensation, Employee Job Satisfaction, and SPSS v26